ANALISIS KARAKTER KEPRIBADIAN TOKOH PADA NOVEL RUMANTI BUKAN PEREMPUAN BIASA KARYA ACHMAD MUNIF (KAJIAN PSIKOLOGI LUDWIG KLAGES) - Amalia Nurul Islami (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2021)
This study aims to describe the temperament, feelings, and power of expression in the novel entitled Rumanti Not An Ordinary Woman by Achmad Munif using Ludwig Klages' personality theory. The focus of this research is on temperament, feelings, and power of expression. Temperament is a trait that exists in every person, Klages divides the temperament into two parts, namely the sanguine temperament and the phlegmatic temperament, and on the focus of feelings Klages also divides it into two parts including mental activity and the level of clarity, then there is the power of expression which is a form of expression for express what is felt in a person such as sad, happy, angry, afraid and disappointed. This study uses a qualitative method, which means that the data are in the form of words and not numbers, besides that this study uses library techniques to obtain data on the research being observed. Data analysis in this study uses hermeutic analysis with various stages, namely reading objects, marking data, coding data, then analyzing all data with Ludwig Klages' personality theory. The results of the research on the novel Rumanti Not Ordinary Women can be concluded that each character in this novel has an interesting temperament, feelings, and expressive power to study.